Arabic and contact-induced change - Lucas, Christopher; Manfredi, Stefano (Language Science Press, 2020)
This volume offers a synthesis of current expertise on contact-induced change in Arabic and its neighbours, with thirty chapters written by many of the leading experts on this topic. Its purpose is to showcase the current state of knowledge regarding the diverse outcomes of contacts between Arabic and other languages, in a format that is both accessible and useful to Arabists, historical linguists, and students of language contact.